Automação no processo de vetorização de áreas de interesse e buffer variável sobre imagens de satélite - Beltrão, Éric Tadiello (2012)
The constant improvement in computer application development techniques, combined with the technological advancement of electronic devices that support such systems, comes with the most contributing significantly different areas of knowledge, adding to these, often, greater accuracy and agility in their processes. Based on this context, and returning our looks for areas of geographic information System (GIS), and Digital image processing, the development of two programs that serve as a proposal of technological innovation as regards the vectorization of areas of interest on satellite images, and creating the buffer variable on the same, this variation that follows the characteristics of width of the area considered. Both programs were developed in the Python programming language and has as final product a shape file containing the vectorization of all areas found in a satellite image by means of classification or filtering. Also presents itself in this work the manipulation of files generated, in order to guide the actions necessary to use, in the best way, the product of these programs, thus helping the user of GIS computer systems for the performance and accuracy of their work.